ATG16L1 Expression in Carotid Atherosclerotic Plaques Is Associated With Plaque Vulnerability. Issue 5 (May 2015) - Magné, Joëlle; Gustafsson, Peter; Jin, Hong; Maegdefessel, Lars; Hultenby, Kjell; Wernerson, Annika; Eriksson, Per; Franco-Cereceda, Anders; Kovanen, Petri T.; Gonçalves, Isabel; Ehrenborg, Ewa
Abstract : Objective—: Autophagy has emerged as a cell survival mechanism critical for cellular homeostasis, which may play a protective role in atherosclerosis. ATG16L1, a protein essential for early stages of autophagy, has been implicated in the pathogenesis of Crohn's disease. However, it is unknown whether ATG16L1 is involved in atherosclerosis. Our aim was to analyze ATG16L1 expression in carotid atherosclerotic plaques in relation to markers of plaque vulnerability. Approach and Results—: Histological analysis of 143 endarterectomized human carotid atherosclerotic plaques revealed that ATG16L1 was expressed in areas surrounding the necrotic core and the shoulder regions. Double immunofluorescence labeling revealed that ATG16L1 was abundantly expressed in phagocytic cells (CD68), endothelial cells (CD31), and mast cells (tryptase) in human advanced plaques. ATG16L1 immunogold labeling was predominantly observed in endothelial cells and foamy smooth muscle cells of the plaques. ATG16L1 protein expression correlated with plaque content of proinflammatory cytokines and matrix metalloproteinases. Analysis of Atg16L1 at 2 distinct stages of the atherothrombotic process in a murine model of plaque vulnerability by incomplete ligation and cuff placement in carotid arteries of apolipoprotein-E-deficient mice revealed a strong colocalization of Atg16L1 and smooth muscle cells only in early atherosclerotic lesions. An increase in ATG16L1 expression and autophagy flux was observed during foam cell formation in human macrophages using oxidized-LDL. Conclusions—: Taken together, this study shows that ATG16L1 protein expression is associated with foam cell formation and inflamed plaque phenotype and could contribute to the development of plaque vulnerability at earlier stages of the atherogenic process. Abstract : Supplemental Digital Content is available in the text.